Research and publication trends: Sports branding on the movie - Hanny Hafiar; Putri Limilia; Ari Agung Prastowo; Kholidil Amin; Davi Sofyan (Universitas Padjadjaran, 2022)
Many films have raised the story of sports as the major story or as the background of a film. However, so far, no research has been obtained that analyzes the mapping of research results related to film and sports. Therefore, this study intends to examine various studies related to film and sports that global researchers have produced. This research uses the bibliometric method. The data source used is the Web of Science, while the tools used to process and display the data are ScientoPy and VosViewer. The results showed that the development of scientific publications starts 2000 to 2021 related to films and sports experienced fluctuating developments. Authors from America and England occupy the top positions for the number of publications. However, in the period 2020 and 2021, researchers from France and Canada are researchers who are more productive in publishing their scientific works. They included most published scientific works related to films and sports in the WoS version of the Social science category. However, Between 2020-2022, more are categorized into the subject of Communication and Film, Radio, & Television. Reference sources widely cited in scientific publications related to film and sports are books by Beeton with the title film-induced tourism (2005) and Crosson's work with the title sport and film (2013). The results of the keyword mapping show that six clusters represent some keywords used by the author in scientific works related to films and sports. In conclusion, sports and cinema research are fully developed in this research.